Legal Protection Of Consumers Related To Breach Of Business Performance - Achmad Faisal; Lamijan Lamijan (Journal Research of Social Science, Economics, and Management, 2023)
. Losses suffered by customers can come from unlawful acts of producers or the existence of a valid contractual relationship between producers and consumers. This study uses an analytical method with an empirical juridical approach or legal sociology, which is an approach to the problem by reviewing the regulations that have been enforced in society as positive law with its implementing regulations including its implementation in the field. Law No. 8 of 1999 concerning Consumer Protection and the Decree of the Minister of Industry and Trade mentions the Dispute Settlement Agency. Based on the explanation of UUPK article 45 paragraph (2) the settlement of consumer disputes as referred to in this paragraph does not rule out the possibility of an amicable settlement by the parties to the dispute. At every stage, efforts are made to use a peaceful settlement by both parties to the dispute. Based on the provisions of Article 45 paragraph (2) UUPK linked to the explanation, consumer dispute resolution can be carried out in the following ways: 1) Peaceful settlement by the parties to the dispute without involving a neutral court or third party; 2) Settlement through court; 3) Settlement out of court through the Consumer Dispute Settlement Agency. In liability based on a default, the obligation to pay compensation is none other than the result of applying the provisions of the agreement, which are legal provisions that both parties voluntarily comply with based on the agreement.